Selective ortho-methylation of phenol with methanol over copper manganese mixed-oxide spinel catalysts - Reddy, A. Satyanarayana; Gopinath, Chinnakonda S.; Chilukuri, Satyanarayana V. (Journal of Catalysis, 2006)
Methylation of phenol with methanol as an alkylating agent to produce 2,6-xylenol was investigated over copper manganese mixed oxide spinels, CuxMn3-xO4 (x = 0, 0.25, 0.5, 0.75, and 1) prepared through co-precipitation. The catalytic activity strongly depends on the composition, acid-base properties, and structural stability. Various parameters, including catalyst composition, reaction temperature, feed composition, and durability of the catalyst during methylation, were investigated. Mainly o-cresol and 2,6-xylenol, along with small amounts of mesitol, were found in the product. A high ortho-selectivity of 100%, with 2,6-xylenol selectivity of 74%, was observed over Cu0.25Mn2.75O4 at 673 K. These catalysts were investigated using various techniques, including BET surface area, XRD, DRS UV-vis, TPD of NH3 and CO2, TPR, and X-ray photoemission spectroscopy (XPS). Powder XRD of the catalysts revealed the formation of copper-manganese spinels with hausmannite (Mn3O4) tetragonal structure, for x = 0-0.5, whereas an increase in copper content (x > 0.5) led to the formation of cubic Cu1.5Mn1.5O4 phase. DRS UV-vis, and FTIR further supported the changes in structural phases observed by XRD. Temperature-programmed desorption Of CO2 and NH3 showed that the catalysts have strong basicity along with weak acidity when x = 0 and 0.25. XPS and XAES analysis revealed the presence of only Cu2+ ions in fresh sample with x = 0.25, whereas for x = 1.0, both Cu1+ and Cu2+ were observed. The deactivation of the catalysts is attributed to structural changes occurring during the reaction. Catalytic activity is correlated with structure, as well as with acid-base properties. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: 2; 6-xylenol; acidity-basicity; copper-manganese oxides; ortho-alkylation; phenol methylation; Spinels

Nanostructured nickel ferrite: a liquid petroleum gas sensor - Darshane, Sonali L.; Suryavanshi, S. S.; Mulla, Imtiaz S. (Ceramics International, 2009)
The present investigation deals with the synthesis of nanostructured nickel ferrite (NiFe(2)O(4)) and their liquid petroleum gas-sensing characteristics. The 15-20 nm size nickel ferrite has been synthesized at 700 degrees C by a simple molten-salt route using sodium chloride as grain growth inhibitor. These nanoparticles exhibit significantly high response towards liquid petroleum gas (LPG) in comparison with ethanol vapor, hydrogen sulfide, ammonia and hydrogen. The gas response towards various gases at their 200 ppm concentrations is investigated at 200-450 degrees C. Different characterization techniques have been employed, such as differential thermal analysis, X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM) and high resolution transmission electron microscopy (HRTEM) to study the crystallite size, structure and morphology. The results suggest possibility of utilization of the nanostructured nickel ferrite, without addition of any precious metal ion, as the LPG detector. (c) 2008 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Ferrites; nanomaterial; Sensor; Spinels